Non-thermal air plasma promotes the healing of acute skin wounds in rats - Kubinova, S; Zaviskova, K; Uherkova, L; Zablotskii, V; Churpita, O; Lunov, O; Dejneka, A (Scientific reports, 2017)
Non-thermal plasma (NTP) has nonspecific antibacterial effects, and can be applied as an effective tool for the treatment of chronic wounds and other skin pathologies. In this study we analysed the effect of NTP on the healing of the full-thickness acute skin wound model in rats. We utilised a single jet NTP system generating atmospheric pressure air plasma, with ion volume density 5 · 1017 m-3 and gas temperature 30-35 °C. The skin wounds were exposed to three daily plasma treatments for 1 or 2 minutes and were evaluated 3, 7 and 14 days after the wounding by histological and gene expression analysis. NTP treatment significantly enhanced epithelization and wound contraction on day 7 when compared to the untreated wounds. Macrophage infiltration into the wound area was not affected by the NTP treatment. Gene expression analysis did not indicate an increased inflammatory reaction or a disruption of the wound healing process; transient enhancement of inflammatory marker upregulation was found after NTP treatment on day 7. In summary, NTP treatment had improved the healing efficacy of acute skin wounds without noticeable side effects and concomitant activation of pro-inflammatory signalling. The obtained results highlight the favourability of plasma applications for wound therapy in clinics.
Keywords: krysa rodu Rattus; Animals; vzduch; Re-Epithelialization; Rats; Plasma Gases; mužské pohlaví; zvířata; signální transdukce; Air; Male; Rats, Wistar; kůže; Skin; plazmové plyny; reepitalizace; potkani Wistar; Signal Transduction